Dance Art Festival produces the best artwork - Siti Nurfarmy, Ibrahim (2021)
PEKAN, 11 April 2021 – The Dance Art Festival (FESERI), Universiti Malaysia Pahang (UMP), finally drew its curtains in an online event recently after being postponed several times due to the Covid-19 pandemic.